Combination of varied agility training with small sided games: How it influences football dribbling skills? - Didi Suryadi; Ardo Okilanda; Novi Yanti; Mikkey Anggara Suganda; Mashud; I Gusti Putu Ngurah Adi Santika; Kadek Dian Vanagosi; Riyan Hardinata (IP Iermakov S.S., 2023)
Background and Study Aim. Dribbling is the ability of a soccer player to carry the ball by kicking it slowly or forcefully. Therefore, special treatment is needed so that the skills of dribbling the ball get better. This study aims to prove the effect of a combination of agility variation exercises with small sided games on soccer dribbling skills. Material and Methods. In this study using the type of experiment design one-group pretest and posttest. The population in this study was Pusaka FC club football athletes. The research sample used purposive sampling so that there were 20 players who were the sample. Data analysis in this study was assisted by using the SPSS Version 26 application. Results. Based on the results of the analysis of the research data above, it shows that there is a difference in the mean value at the pretest of 21.85 and the mean value of the posttest of 17.48 thus showing an increase that occurred, namely by 4.37. Based on the results of the significance value obtained 0.000 <0.05 then the data shows that the combination of variations in agility training and small training sided games have a significant effect on dribbling skills in soccer games. Conclusions. The results prove that the combination of agility variation exercises with small sided games have a significant effect on football dribbling skills. Based on these results, a combination of agility variation exercises with zig-zag runs can be implemented to improve dribbling skills soccer player.